Follicular Lymphoma of the Gallbladder in an Octogenarian: A Case Report and Literature Review - Mikayla Myers MD; Bassel Dakkak MD; Swapna Sirigireddy MD; Ibrahim Shanti MD; Drew Ferguson MD; Abdelwahap Elghezewi MD; Mustafa Ben Khayal MD; Zakaria Alagha MD, MSc; Ahmed Sherif MD, AGAF, FASGE; Eva-Pattont Tackett MD, FACP (Journal of Investigative Medicine High Impact Case Reports)
Primary follicular lymphoma (PFL) is an indolent subtype of non-Hodgkin lymphoma that typically involves lymphoid tissues. Gallbladder involvement is exceedingly rare and poses significant diagnostic challenges. Few cases in the literature describe gallbladder follicular lymphoma, particularly in elderly male patients, leaving notable gaps in clinical understanding and management. Herein, we present the case of an 82-year-old male who presented with acute abdominal pain and unintentional weight loss. Initial imaging, including contrast-enhanced computed tomography, ultrasound, and magnetic resonance imaging, revealed a suspicious gallbladder mass with wall thickening and regional lymphadenopathy, raising concern for malignancy. Endoscopic ultrasound-guided fine needle aspiration and subsequent immunophenotyping confirmed a diagnosis of PFL. The patient underwent radical cholecystectomy with lymphadenectomy, and histopathological examination corroborated the diagnosis of gallbladder follicular lymphoma. During follow-up, the patient developed complications, yet no evidence of lymphoma recurrence was observed. A literature review identified 8 similar cases, further emphasizing the rarity of this presentation. Future research should focus on optimizing diagnostic techniques, refining therapeutic strategies, and conducting longer-term follow-up studies to better assess patient outcomes in such a rare disease. This case highlights the need for heightened clinical suspicion and comprehensive evaluation in atypical presentations of extranodal lymphoma.